Feedback Linearization of RF Power Amplifier for TETRA Standard - Asif Ahmed (Institute of Advanced Engineering and Science, 2014)
In wireless transmission systems, non-ideal response of different functional components along with power amplifier’s nonlinearity plays a major role in degrading the transmitter performance. Several parameters defines the performance of a wireless transmitter, such as adjacent channel power ratio (ACPR), error vector magnitude (EVM), spectral mask, etc., and the effect of non-ideal behaviour of the transmitter affects these parameters. For many standards these parameter specifications are defined such that the concern for transmitter linearization is very much relaxed. Standards like Terrestrial Trunked Radio (TETRA) specify strict regulation on these parameters. Therefore, the requirement of linearity is a great challenge for the design of the transmitter. Many linearization schemes is available for linearizing the nonlinear effect of a transmitter, and among those the Cartesian feedback technique is a well known concept for linearization of transmitter operating according to TETRA standard, as well as employing a narrowband operation. In our research, distortion effect of the transmitter has been analysed, and a practical demonstration of the linearization effect over distortion has been implemented using the Cartesian feedback concept.